Cisplatin overcomes Bcl-2-mediated resistance to apoptosis via preferential engagement of Bak: critical role of Noxa-mediated lipid peroxidation - Kütük, Özgür; Tezil, Tuğsan; Shoshan, Maria C.; Başağa, Hüveyda; ARISAN, ELİF DAMLA (Oxford University Press, 2009)
Increased expression of antiapoptotic Bcl-2 proteins confers therapeutic resistance in various cancer types. Targeting Bcl-2 proteins by small molecules or activating alternative pathways to bypass Bcl-2-mediated protection to promote apoptosis are two approaches to overcoming therapeutic resistance. Here, we show that cisplatin triggers a Bak-dependent pathway to induce apoptosis in Bcl-2-overexpressing MCF-7 cells. p53-mediated induction of Noxa expression, generation of lipid peroxidation end products and induction of Noxa–Mcl-1 interaction are necessary for this pathway to function. Although Puma is also induced by cisplatin treatment, it is not required for apoptosis. Similarly, reactive oxygen species production by cisplatin did not have any effect on cisplatin-induced apoptosis in MCF-7 Bcl-2 cells. Furthermore, p53 promotes cisplatin-induced apoptosis by directly binding and counteracting Bcl-x L antiapoptotic function. In conclusion, our findings suggest a novel mode of action for cisplatin to overcome Bcl-2-mediated protection against apoptosis, which requires preferential activation of Bak and p53-mediated upregulation of Noxa protein levels and lipid peroxidation.
Keywords: INDUCED CELL-DEATH; OXIDATIVE STRESS; CANCER-CELLS; MITOCHONDRIAL APOPTOSIS; BH3-ONLY PROTEINS; HYDROGEN-PEROXIDE; IN-VIVO; BCL-2; P53; ACTIVATION; apoptosis; cisplatin; bcl2 gene; lipid peroxidation; mcf-7 cells; Cancer Biology